Pyrogenic bacteria - Groome, Herbert Revere (My University, 1905)
Introduction: In earlier modern time it was supposed that in all pus formations there existed bacteria, and that three organisms were the cause of the pus formation, but by later experiments it has been proven that bacteria are not in all cases present. Organisms which produce pus have been grouped by themselves and called phytogenic bacteria. By experiments performed by Growety, DeBasy, Steinhaus, Kaufin and other it was conclusively proven that certain chemical substances injected beneath the skin give rise to pus formation without presence of bacteria. Pasteur proved in 1878 that sterilized culture of pus cocci produced pus formation when injected subcutaneously. This fact has also been confirmed by a number of bacteriologists as regards various bacilli. Buchner proved that the so-called pus forming property was due to the bacterial cells and not to any chemical production by the living cells. To prove this Buchner filtered a pus producing organism through a Chamberlain filter; the filtrate which passed through was of no effect when injected subcutaneously, but the dead bacterial cells retained by the filter produced aseptic pus. Buchner then made further experiments to prove the cause of pus formation and his conclusion was that it is due to the albuminous contents of the bacterial cells. Though it has been conclusively proven that a large number of micro-organisms may cause the formation of pus, the extended research of numerous prominent bacteriologists prove that but few species are concerned in the formation of abscesses and ulcers troublesome to man.
Citation: Groome, Herbert Revere. Pyrogenic bacteria. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Steril culture; Pus Cocci; Stuphylococus Pyogenes Aureus; Theses